2019
DOI: 10.3390/electronics9010019
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Driving Style Identification of Truck Drivers in Open-Pit Mines

Abstract: The significance in constructing a driving style identification model for open-pit mine truck drivers is to reduce diesel consumption and improve training. First, we developed a driving behavior and mining truck condition monitoring system for an open-pit mine. Under heavy-load and no-load conditions of a mining truck, based on the same experimental truck and haulage road, the data of driving behavior and truck status of different drivers were collected. The driving style characteristic parameters of mining tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In the study [39], it was found that the fuelsaving driving skills of truck drivers are a significant factor in reducing fuel usage. And according to Wang et al [40], the fuel consumption of aggressive driving styles affects the average fuel consumption by 10%.…”
Section: Results Obtained From Eco-truck Driving Skills Training Programmentioning
confidence: 99%
“…In the study [39], it was found that the fuelsaving driving skills of truck drivers are a significant factor in reducing fuel usage. And according to Wang et al [40], the fuel consumption of aggressive driving styles affects the average fuel consumption by 10%.…”
Section: Results Obtained From Eco-truck Driving Skills Training Programmentioning
confidence: 99%
“…In addition, DILISP can collect the sport appearance of two vehicles and record the drivers actions. Qun Wang et al [3] designed a data acquisition system based on an inertial navigation sensor and advanced RISC machine microcontroller that can collect the driver's driving behavior and vehicle status in real time. Derick A. Johnson et al [4] collected the speed and direction data of the vehicle during driving using the rear camera, accelerometer, gyroscope, and GPS of a smartphone.…”
Section: Related Work 21 Data Acquisitionmentioning
confidence: 99%
“…CNN, long short-term memory (LSTM) network, and pre train-LSTM [15], [17], [20], random forest [16] - [14], [17], [20]/+ [15], [16] -+ + Application of self-organizing maps [21] + + Classification method, which is enabled by ensemble learning [23] --+ +…”
Section: Introductionmentioning
confidence: 99%